Archivist in the Digital Age: The Basic Competencies and Roles an Archivist Should Have - İnceoğlu, Seher and Şentürk, Burçak (Information World, 2014)
Information age or digital age has come into our lives with 21st century, archival sceince has begun to be implemented playing physical and electronic media along with development of the technology and it has brought new dimensions. Archival science which examination of the previous and current status especially in this era of archival science seems important to define identificaiton of applications in area and new elements at concept of archive and archivist. In this context, 150 participants who position of archivist have applied survey. It has been targeted revealing of archivist of the changing job descriptions and responsibilities by received with data.